Prevalence of papular urticaria caused by flea bites and associated factors in children 1-6 years of age in Bogotá, D.C. (2017)
Background: Papular urticaria is a chronic inflammatory disease caused by exposure to arthropod bites. The disease has been reported in children attending medical centers, but the causes as the risk factors associated with the disease have not been established. The objective of this study was to determine the prevalence of papular urticaria caused by flea bite and identify the risk factors in children between 1 to 6 years of age in Bogotá D.C, between March 2009 and June 2011. Methods: A cross-sectional, two-stage, clustered study using random probability sampling and stratified with proportional allocation was carried out in children (1-6 years of age) in educational institutions in Bogotá D.C. to determine the prevalence of the disease. Children underwent a dermatological examination by general practitioners with a previous training. Furthermore, digital photographs of skin lesions were taken for further confirmation of the diagnosis by dermatologists. A structured survey was completed by the parents or caregivers, and it was evaluated using an unconditional logistic regression to identify factors associated with the disease. Results: A total of 2437 children were included in the study. The prevalence of papular urticaria caused by flea bite in this population was 20.3% (CI 95%: 18.2 to 22.5%). The major risk factors associated with the disease were the presence of fleas in households (OR 1.74, CI 95%: 1.35 to 2.25), using mattresses without springs (OR 1.73, CI 95%: 1.20 to 2.50), the use of daily public transportation to carry the children to the educational institutions (OR 1.76, CI 95%: 1.07 to 2.89), having a soil/earth floor in the main bedroom (OR 6.81, CI 95%:1.16-39.96), and having siblings with a history of atopic dermatitis (OR 1.76 CI 95%: 1.07-2.89). Conclusions: A high prevalence of papular urticaria caused by flea bite was found in Bogotá D.C. The main factors associated with the disease might be modified with the implementation of prevention, control strategies in housing, educational institutions, and public transportation. © 2017 The Author(s).